More than words : transforming script, agency, and collective life in Bali - Fox, Richard, 1972- (Cornell University Press, 2018)
"Challenges conventional understandings of textuality and writing as they pertain to the religious traditions of Southeast Asia, through ethnographic and archival research conducted on Bali"--